Analysis and control of heteroepitaxial systems. (March 2015) - McGill, J.A.; Abukhdeir, N.M.; Ogunnaike, B.A.; Vlachos, D.G.
Abstract : Highlights: We introduce a novel method for selecting process outputs for underdefined systems. We demonstrate that control of thin-film surface patterns is achievable with simple PI controllers. We show that simple controllers can drive self-assembly into regimes resulting in favorable patterns. We use PCA to reduce correlated pattern metrics into uncorrelated, low-dimensional projections. Abstract: In this work, we present a method of controlling self-assembly. First, we demonstrate that images of surface morphologies can be decomposed into important features that capture essential properties of the surface. Subsequently, we develop a method for obtaining a low-dimensional representation of the entire feature set and show that this reduced representation can be used as a set of surrogate process outputs for process control and design of thin-films. Finally, the effectiveness of this approach is demonstrated in several simulation studies that utilize two macroscopic manipulated variables known to influence the self-assembly of thin-films, temperature and repulsion strength, to drive arbitrary patterns toward a target morphology.